IMPLEMENTASI SISTEM INFORMASI KULIAH ONLINE TERHADAP MINAT MENGAJAR DAN IMPLIKASINYA TERHADAP KUALITAS MENGAJAR DOSEN (Kasus Pada Dosen Tetap Unikom Bandung) - Umi Narimawati (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
AbstractLack of utilization of Online Course Information Systems in attracting lecturer‟s interest to use it, whereas the online course is conducted as one effort to improve the quality of lecturer‟s teaching. Online course is expected to fulfill the information needs of students from the lecturer related to lecture material and the occurrence of effective communication between lecturers and students. The purpose of this study is to analyze the implementation of information systems online course towards interest of lecturer in teaching and its implications on the quality of the lecturer‟s teaching at the Universitas Komputer Indonesia of Bandung. The method used in this study is qualitative and quantitative methods. The technique of collecting data by observation, interviews and questionnaire. The unit analysis in this research are UNIKOM permanent lecturers numbering 100 people with students numbering 500 people as the sample. Statistical testing using path analysis with an application program SPSS17.0 for windows.The results showed that the implementation of information systems online lecture in UNIKOM Bandung as a whole is included in good criteria, but the infrastructure indicators still show the less good criteria due to lack of facilities of personal computers and slow internet access for lecturers. Also supported by the bandwidth limitations that have not been sufficient to access simultaneously.As for the variables of lecturer‟s interest included in the moderate category. While the variable quality of the lecturer‟s teaching included in the high category, unless the attraction indicator is less to respond, it is caused by the less interesting material design or materials which uploaded by the lecturer to student. The result of analysis showed that the implementation of online course have a positive and significant impact on the interest and quality of the lecturer‟s teaching. The largest contribution to the quality of lecturer‟s teaching come from lecturer‟s interest. But then the simultaneous influence is more than partial. This means the existence of an online course information system should indeed align with the lecturer‟s desire to create interest as well as lecturer‟s teaching quality.Keywords :Information System, Online Course, Lecturer‟s Interest, Lecturer‟s Teaching Quality